THE IMPORTANCE OF PIBID FOR THE INITIAL TRAINING OF CHEMISTRY TEACHERS AT FACULDADE DE EDUCAÇÃO DE CRATEÚS – FAEC - Nunes Pereira Avelino, Paulo; Nayara Mascarenhas Lima, Jessyca; Lacerda Junior, Orivaldo (Journal of Interdisciplinary Debates, 2023)
The exercise of teaching practice is strongly developed in undergraduate courses through teacher training programs, such as the Institutional Scholarship Program for Teaching Initiation (PIBID). And during the participation of future teachers in institutional programs, their first didactic impressions are created, as, for many, admission to the scholarship is done in the initial phase of the course, thus, this will be their first contact with the school context. In this way, PIBID enables undergraduate students to immerse themselves in the educational field even in the initial semesters, allowing them to act within their future field of work, which is the classroom. Being possible to develop and carry out activities that will be fundamental in your training. Given the above, this work aims to analyze the impact of PIBID on the initial training of teachers, especially students from the Faculty of Education of Crateús (FAEC), and to analyze the disadvantages of students who did not participate in PIBID. A bibliographical research was carried out for the theoretical foundation of this research and a field research, in which interviews were carried out with 22 FAEC students, 11 of which were former PIBID students from September 2018 to November 2019, and 11 students who did not participate in the program. To collect data for this research, a questionnaire was applied to these two audiences with questions, we divided the questions of students who had experience in PIBID (5 questions) and students who did not participate in PIBID (4 questions), with 3 questions being equal in both questionnaires. According to the bibliographic study and field research, the main data obtained found that the PIBID is very important for initial teacher education, making it essential that undergraduate students participate in the program, but not everyone has this opportunity to participate, as places are not enough for all students.